PERAN KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU - Ade Akhmad Saputra; Nabilah, Nabilah Anggraeni; Arwan (AL-MAFAZI: JURNAL MANAJEMEN PENDIDIKAN ISLAM, 2024)
This research aims to find out the role of the principal in increasing the professionalism of teachers at SD Negeri 1 Pematang Kijang. The research method used is a descriptive qualitative method using data collection techniques in the form of observation, interviews and documentation studies with emphasis on informant data sources, namely the principal, deputy principal and teachers at SD Negeri 1 Pematang Kijang. From the results of this research to the principal at SD Negeri 1 Pematang Kijang, he hopes that teachers will carry out their role as teachers more in accordance with their responsibilities as educators. The solution given by the principal to increase teacher professionalism is by providing motivation to teachers and also holding evaluation meetings.